Pomegranite concentrate and preparation method thereof, composition for cement-based adhesive, cement-based adhesive and application of cement-based adhesive

The garnet concentrate is prepared through initial selection of spiral chutes and shaker, combined with weak magnetic separation, which solves the problems of low resource utilization and high cost in the existing technology, and realizes the garnet concentrate in cement-based adhesives. Efficient application, excellent mechanical properties and the effect of reducing production costs.

CN119461918APending Publication Date: 2025-02-18HUNAN ZOOMLION NEO MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411538634.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the application of garnet micro powder as filler in epoxy resin adhesives, the comprehensive utilization rate of resources is low and requires strong magnetic separation and purification, which is relatively high.

Method used

Through spiral chute primary selection and shaker re-selecting, combined with weak magnetic separation, garnet concentrate is prepared, containing 60-80% garnet and 15-30% quartz and other components, and applied to cement-based In adhesives, they are aggregates and fillers.

Benefits of technology

It improves the comprehensive utilization rate of tailings, reduces production costs, and the prepared cement-based adhesive has excellent properties that exceed the standard requirements, and is suitable for the field of ceramic tile adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112233580000091
    Figure BDA0005112233580000091
  • Figure BDA0005112233580000101
    Figure BDA0005112233580000101
  • Figure BDA0005112233580000111
    Figure BDA0005112233580000111
Patent Text Reader

Abstract

The invention relates to the field of mineral processing, and discloses garnet concentrate and a preparation method thereof, a composition for a cement-based adhesive, the cement-based adhesive and application of the cement-based adhesive, and the garnet concentrate contains the following components in percentage by mass: 60-80% of garnet, 15-30% of quartz, 3-5% of feldspar, 1-2% of calcite and 0-2% of fluorite. The invention discloses an iron-based composite material which comprises the following components in percentage by weight: 0-1% of iron, 0-1% of mica, 0-1% of argillaceous mineral, 0-0.5% of sulfide mineral of iron and 0-0.5% of non-sulfide mineral of iron. The garnet concentrate provided by the invention is applied to the ceramic tile adhesive as aggregate and filler, and compared with a traditional scheme adopting quartz sand, the prepared ceramic tile adhesive product has equivalent and even better performance, the production cost of a cement-based adhesive is reduced, and the comprehensive utilization rate of tailings is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of mineral processing, and in particular to a garnet concentrate and a preparation method thereof, a composition for a cement-based adhesive, a cement-based adhesive and applications thereof. Background Art

[0002] Most of the skarn-type tungsten tailings in my country contain a large amount of garnet, and some tailings contain garnet as the main component. Garnet is divided into six types: iron-aluminum, magnesium-aluminum, manganese-aluminum, calcium-aluminum, calcium-iron, and calcium-chromium. Among them, iron-aluminum garnet is mainly used as an abrasive, but most of the tungsten tailings are calcium-iron and calcium-aluminum garnet, which have a fine particle size and a lower hardness than iron-aluminum garnet, and cannot be used as an abrasive. Due to insufficient understanding of other uses of garnet, garnet is basically stored in the tailings pond like other tailings. At the same time, the construction of tailings ponds has also increased the production and environmental protection costs of enterprises. The storage space required for a large amount of tailings and potential environmental hazards have become problems that mining companies need to solve urgently.

[0003] CN104099035A discloses the application of garnet powder as filler in epoxy resin adhesive and an epoxy resin adhesive, wherein the raw material is garnet tailings, and a gravity separation-magnetic separation-classification combined process is used to recover garnet powder with a particle size of ≤0.045 mm, and the garnet mineral content reaches more than 60%, which is used as a refined filler in the epoxy resin adhesive. When garnet powder is used as a filler in epoxy resin adhesive, the filling amount can reach more than 60%, and the prepared epoxy resin adhesive has the performance of the adhesive and concrete repair material indicators in GB50367-2006 "Concrete Structure Reinforcement Design Code", and has the advantages of improving wear resistance, compression resistance, and corrosion resistance, reducing material costs, and having a large development space and market prospects in the application of epoxy resin adhesives. However, the prior art requires purification through strong magnetic separation, and only garnet powder with a particle size of ≤0.045 mm is used after purification, while garnet powder with a particle size of >0.045 mm is not used, and the comprehensive utilization rate of resources is low. Summary of the invention

[0004] The purpose of the present invention is to provide a tailings purification method with high comprehensive utilization rate, and to provide a ceramic tile adhesive product with low cost and excellent mechanical properties.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a garnet concentrate, which contains the following components in mass percentage: 60-80% garnet, 15-30% quartz, 3-5% feldspar, 1-2% calcite, 0-2% fluorite, 0-1% mica, 0-1% mud minerals, 0-0.5% iron sulfide minerals, and 0-0.5% iron non-sulfide minerals.

[0006] A second aspect of the present invention provides a method for preparing garnet concentrate, the method comprising:

[0007] (1) subjecting the tungsten tailings to primary selection in a spiral chute and secondary selection in a shaking table in sequence to obtain concentrate I and tailings I; and controlling the conditions so that the content of mud minerals in the concentrate I is ≤1.0wt%;

[0008] (2) subjecting the concentrate I to a first weak magnetic separation and a second weak magnetic separation in sequence to obtain a garnet concentrate; the magnetic field strength of the first weak magnetic separation is 0.2-0.4T, and the magnetic field strength of the second weak magnetic separation is 0.45-0.6T.

[0009] The third aspect of the present invention provides a cement-based adhesive composition, which contains the following components in percentage by mass: 60-72% of garnet concentrate, 28-35% of cement, 0.1-0.4% of cellulose ether, and 1-2% of dispersible rubber powder;

[0010] The garnet concentrate is the garnet concentrate described in the first aspect, or is the garnet concentrate prepared by the method described in the second aspect.

[0011] The fourth aspect of the present invention provides a cement-based adhesive, which is prepared by mixing a cement-based adhesive composition with water; the cement-based adhesive composition is the cement-based adhesive composition described in the third aspect.

[0012] The fifth aspect of the present invention provides the use of the cement-based adhesive described in the fourth aspect in the field of ceramic tile adhesives.

[0013] The technical solution provided by the present invention has at least the following advantages:

[0014] (1) The present invention does not need to further purify the garnet concentrate by strong magnetic separation, and the non-magnetic impurities in the garnet, such as quartz, calcite, and fluorite, will not have an adverse effect on the product performance itself. Without the last step of strong magnetic separation and purification, the comprehensive utilization rate of the tailings is further improved.

[0015] (2) The garnet concentrate provided by the present invention is applied to tile adhesive as an aggregate and filler. The components in the garnet concentrate work together to produce a tile adhesive product having equivalent or even better performance than the traditional solution using quartz sand. However, quartz sand is expensive. The present invention can significantly reduce the production cost of tile adhesive.

[0016] (3) The tile adhesive provided by the present invention has excellent performance that exceeds the standard requirements of C1-ordinary cement-based adhesive in JC / T547-2017 ceramic tile adhesive. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] The "40-70 mesh" in the present invention refers to the particle size range of particles that can pass through the 40-mesh Chinese standard sieve but cannot pass through the 70-mesh Chinese standard sieve. The "70-140 mesh" refers to the particle size range of particles that can pass through the 70-mesh Chinese standard sieve but cannot pass through the 140-mesh Chinese standard sieve. The "below 140 mesh" refers to the particle size range of particles that can pass through the 140-mesh Chinese standard sieve. Other similar expressions in the present invention have the same definition as this.

[0019] As described above, the first aspect of the present invention provides a garnet concentrate, which contains the following components in mass percentage: 60-80% garnet, 15-30% quartz, 3-5% feldspar, 1-2% calcite, 0-2% fluorite, 0-1% mica, 0-1% mud minerals, 0-0.5% iron sulfide minerals, and 0-0.5% iron non-sulfide minerals.

[0020] Preferably, the mud mineral is selected from at least one of chlorite, kaolin and illite.

[0021] Preferably, the iron sulfide mineral is selected from at least one of pyrite and pyrrhotite.

[0022] Preferably, in the iron sulfide mineral, the mass content of total sulfur is less than 0.1%.

[0023] Preferably, the non-sulfide iron mineral is selected from at least one of limonite, hematite and magnetite.

[0024] The present invention has no particular restrictions on the particle size of each component in the garnet concentrate. The particle size of a single component is preferably randomly distributed within a range below 40 meshes to form the garnet concentrate product of the present invention. The particle size distribution of the garnet concentrate of the present invention preferably satisfies: the particle size content of 40-70 meshes is 45-55wt%, the particle size content of 70-140 meshes is 35-40wt%, and the particle size content below 140 meshes is 10-15wt%.

[0025] As mentioned above, the second aspect of the present invention provides a method for preparing garnet concentrate, the method comprising:

[0026] (1) subjecting the tungsten tailings to primary selection in a spiral chute and secondary selection in a shaking table in sequence to obtain concentrate I and tailings I; and controlling the conditions so that the content of mud minerals in the concentrate I is ≤1.0wt%;

[0027] (2) subjecting the concentrate I to a first weak magnetic separation and a second weak magnetic separation in sequence to obtain a garnet concentrate; the magnetic field strength of the first weak magnetic separation is 0.2-0.4T, and the magnetic field strength of the second weak magnetic separation is 0.45-0.6T.

[0028] Preferably, in step (1), the conditions are controlled so that the content of mud minerals in the concentrate I is ≤0.8wt%, more preferably ≤0.6wt%.

[0029] According to a preferred embodiment, the operation in step (1) includes:

[0030] S1: using a spiral chute to sequentially perform a first roughing and a first concentrating on the tungsten tailings to obtain a concentrate I-1 and a tailing I-1; controlling the conditions so that the content of mud minerals in the concentrate I-1 is ≤6.0wt%;

[0031] S2: using a shaking table to perform a second roughing and a second cleaning on the concentrate I-1 in sequence to obtain the concentrate I and the tailings I.

[0032] Preferably, in step S1, the conditions are controlled so that the content of mud minerals in the concentrate I-1 is ≤5.5wt%, particularly preferably ≤5.0wt%.

[0033] Preferably, in step S1, the conditions of the first roughing and the first cleaning are independently satisfied: the feed concentration is 25-35wt%, the spiral chute flushing volume is 0.8-1.2t / h, and the feed dry ore volume is 0.2-0.5t / h.

[0034] Preferably, in step S1, the flushing volume of the spiral chute of the first roughing is lower than that of the first concentrating, and the dry ore feeding volume of the first roughing is higher than that of the first concentrating. The inventors found in the study that the yield of garnet concentrate obtained under the preferred conditions is higher, and the ceramic tile adhesive prepared using the garnet concentrate has more excellent mechanical properties.

[0035] Preferably, in step S2, the conditions of the second roughing and the second cleaning are independently satisfied: the feed concentration is 15-25wt%, the shaking table flushing volume is 0.1-0.5t / h, and the feed dry ore volume is 0.05-0.1t / h.

[0036] Preferably, in step S2, the water flushing volume of the shaking table of the second roughing is lower than that of the second concentrating, and the dry ore feeding volume of the second roughing is higher than that of the second concentrating. The inventors found in the study that the yield of garnet concentrate obtained under the preferred conditions is higher, and the ceramic tile adhesive prepared using the garnet concentrate has better mechanical properties.

[0037] Preferably, in step (1), the tungsten tailings contains the following components in mass percentage: 40-45% garnet, 28-35% quartz, 5-10% feldspar, 1-3% calcite, 2-3% fluorite, 1-1.5% mica, 7-10% argillaceous minerals, 1-3% iron sulfide minerals, and 0.5-1.5% iron non-sulfide minerals.

[0038] The garnet concentrate or the tungsten tailings described in the present invention may also contain other substances in addition to the listed components. The content of the other substances is preferably not more than 2%, and more preferably not more than 1%.

[0039] The preparation method of the garnet concentrate of the present invention may also include conventional post-processing means in the art. For example, the intermediate product obtained after the second weak magnetic separation is dried to obtain the garnet concentrate, and then the garnet concentrate is subjected to particle size screening and grading treatment to obtain garnet concentrates of different particle sizes to meet actual use needs. The present invention will not be described in detail here, and those skilled in the art should not be construed as limiting the present invention.

[0040] As mentioned above, the third aspect of the present invention provides a cement-based adhesive composition, which contains the following components by mass percentage: 60-72% of garnet concentrate, 28-35% of cement, 0.1-0.4% of cellulose ether, and 1-2% of dispersible rubber powder;

[0041] The garnet concentrate is the garnet concentrate described in the first aspect, or is the garnet concentrate prepared by the method described in the second aspect.

[0042] Preferably, the cement-based adhesive composition contains the following components by mass percentage: 33-37% of 40-70 mesh garnet concentrate, 24-27% of 70-140 mesh garnet concentrate, 3-8% of 140 mesh or less garnet concentrate, 28-35% of cement, 0.1-0.4% of cellulose ether, and 1-2% of dispersible rubber powder. The inventors found in their research that the cement-based adhesive prepared under the preferred conditions has better weather resistance and adhesion.

[0043] Preferably, the cement is ordinary Portland cement with a strength grade of 42.5.

[0044] Preferably, the cellulose ether is hydroxypropyl methylcellulose, and the viscosity of the hydroxypropyl methylcellulose is in the range of 50,000-100,000 mpa·s.

[0045] The viscosity of the cellulose ether of the present invention is measured according to the Brookfield RV viscometer standard, 2% concentration neutral solution, 20° C., and 20 rpm.

[0046] Preferably, the dispersible rubber powder is vinyl acetate ethylene copolymer.

[0047] The fourth aspect of the present invention provides a cement-based adhesive, which is prepared by mixing a cement-based adhesive composition with water; the cement-based adhesive composition is the cement-based adhesive composition described in the third aspect.

[0048] Preferably, the mass ratio of the cement-based adhesive composition to the water is 100:25-29.

[0049] The fifth aspect of the present invention provides the use of the cement-based adhesive described in the fourth aspect in the field of ceramic tile adhesives.

[0050] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0051] Tungsten tailings composition: 43wt% garnet, 31wt% quartz, 8wt% feldspar, 2wt% calcite, 2.3wt% fluorite, 1.2wt% mica, 8.5wt% mud minerals (chlorite, kaolin, illite), 2wt% iron sulfide minerals (pyrite, pyrrhotite), 1wt% iron non-sulfide minerals (limonite, hematite, magnetite), 1wt% other substances.

[0052] Cement: ordinary Portland cement with strength grade 42.5;

[0053] Cellulose ether: purchased from Shanghai Huiguang Fine Chemical Co., Ltd., brand name GMC3112D;

[0054] Dispersible rubber powder: purchased from Wacker Chemical Company of Germany, brand number 5010N.

[0055] Preparation Example 1

[0056] S1: First, the tungsten tailings are slurried to a concentration of 25wt%, and fed into a spiral chute for the first roughing selection (the water flow of the spiral chute is 0.8t / h, and the dry ore feeding amount is 0.5t / h), and three products of rough concentrate, middlings, and tailings are produced; the rough concentrate and the middlings are mixed to form intermediate minerals, which are fed into a spiral chute for the first selection (the ore concentration is 25wt%, the water flow of the spiral chute is 1.2t / h, and the dry ore feeding amount is 0.2t / h), and three products of rough concentrate, middlings, and tailings are produced; the rough concentrate and the middlings are mixed to form concentrate I-1 (the mud mineral content is 5.0wt%).

[0057] S2: The above-mentioned concentrate I-1 is sent to a shaking table for a second roughing selection (the feed concentration is 15wt%, the shaking table flushing volume is 0.1t / h, and the feed dry ore volume is 0.1t / h), and four products of rough concentrate, middling 1, middling 2, and tailings are produced; the rough concentrate, middling 1 and middling 2 are mixed to form intermediate minerals, which are fed into a shaking table for a second selection (the feed concentration is 20wt%, the shaking table flushing volume is 0.3t / h, and the feed dry ore volume is 0.07t / h), and four products of rough concentrate, middling 1, middling 2, and tailings are produced. The middling 2 and tailings are mixed to form the final tailings, and the rough concentrate and middling 1 are mixed to form concentrate I (the mud mineral content is 0.6wt%).

[0058] S3: The concentrate I is sequentially subjected to a first weak magnetic separation (magnetic field strength 0.3T) and a second weak magnetic separation (magnetic field strength 0.5T) to obtain a garnet concentrate.

[0059] Preparation Example 2

[0060] S1: First, the tungsten tailings are slurried to a concentration of 30wt%, and fed into a spiral chute for the first roughing (the water flow of the spiral chute is 0.8t / h, and the dry ore feeding amount is 0.5t / h), and three products of rough concentrate, middlings, and tailings are produced; the rough concentrate and the middlings are mixed to form intermediate minerals, which are fed into a spiral chute for the first concentration (the feed concentration is 30wt%, the water flow of the spiral chute is 1.2t / h, and the dry ore feeding amount is 0.2t / h), and three products of rough concentrate, middlings, and tailings are produced; the rough concentrate and the middlings are mixed to form concentrate I-1 (the mud mineral content is 5.8wt%).

[0061] S2: The above-mentioned concentrate I-1 is fed into a shaking table for a second roughing selection (the feed concentration is 20wt%, the shaking table flushing volume is 0.2t / h, and the feed dry ore volume is 0.08t / h), and four products of rough concentrate, middling 1, middling 2, and tailings are produced; the rough concentrate, middling 1, and middling 2 are mixed into intermediate minerals, which are fed into a shaking table for a second selection (the feed concentration is 25wt%, the shaking table flushing volume is 0.5t / h, and the feed dry ore volume is 0.05t / h), and four products of rough concentrate, middling 1, middling 2, and tailings are produced. The middling 2 and tailings are mixed into the final tailings, and the rough concentrate and middling 1 are mixed to form concentrate I (the mud mineral content is 0.7wt%).

[0062] S3: The concentrate I is sequentially subjected to a first weak magnetic separation (magnetic field strength 0.4 T) and a second weak magnetic separation (magnetic field strength 0.6 T) to obtain a garnet concentrate.

[0063] Preparation Example 3

[0064] S1: First, the tungsten tailings are slurried to a concentration of 35wt%, and fed into a spiral chute for the first roughing (the water flow of the spiral chute is 1.0t / h, and the dry ore feeding amount is 0.4t / h), and three products of rough concentrate, middlings, and tailings are produced; the rough concentrate and the middlings are mixed to form intermediate minerals, which are fed into a spiral chute for the first concentration (the ore concentration is 35wt%, the water flow of the spiral chute is 1.2t / h, and the dry ore feeding amount is 0.2t / h), and three products of rough concentrate, middlings, and tailings are produced; the rough concentrate and the middlings are mixed to form concentrate I-1 (the mud mineral content is 6.2wt%).

[0065] S2: The above-mentioned concentrate I-1 is fed into a shaking table for a second roughing selection (the feed concentration is 25wt%, the shaking table flushing volume is 0.2t / h, and the feed dry ore volume is 0.08t / h), and four products of rough concentrate, middling 1, middling 2, and tailings are produced; the rough concentrate, middling 1, and middling 2 are mixed into intermediate minerals, which are fed into a shaking table for a second selection (the feed concentration is 25wt%, the shaking table flushing volume is 0.5t / h, and the feed dry ore volume is 0.05t / h), and four products of rough concentrate, middling 1, middling 2, and tailings are produced. The middling 2 and tailings are mixed into the final tailings, and the rough concentrate and middling 1 are mixed to form concentrate I (the mud mineral content is 0.8wt%).

[0066] S3: The concentrate I is sequentially subjected to a first weak magnetic separation (magnetic field strength 0.2T) and a second weak magnetic separation (magnetic field strength 0.45T) to obtain a garnet concentrate.

[0067] Preparation Example 4

[0068] A similar process to Example 1 was adopted, except that in step S1, the conditions of adjusting the flushing amount of the spiral chute of the first concentration and the amount of dry ore fed were the same as those of the first roughing, and a concentrate I-1 (with a mud mineral content of 6.2 wt%) was obtained;

[0069] In step S2, the conditions of the water flushing amount and the dry ore feeding amount of the second concentrator are adjusted to be the same as those of the second rougher, and concentrate I (with a clay mineral content of 1.0 wt%) is obtained;

[0070] The other conditions remain unchanged to obtain garnet concentrate.

[0071] The composition of the garnet concentrate obtained in the above preparation example is shown in Table 1.

[0072] Table 1

[0073]

[0074]

[0075] Example 1

[0076] The garnet concentrate obtained in the above preparation example is dried, sieved and graded using a Chinese standard sieve to obtain 40-70 mesh garnet concentrate, 70-140 mesh garnet concentrate and 140 mesh or less garnet concentrate in turn; the concentrates are uniformly mixed with cement, cellulose ether and dispersible rubber powder, and then mixed with water to obtain a cement-based adhesive.

[0077] Embodiment 2-5

[0078] The process is similar to that of Example 1, except that the types and amounts of the components are different, as shown in Table 2.

[0079] Example 6

[0080] The garnet concentrate J1 obtained above is dried, sieved and graded using a Chinese standard sieve to obtain 50-100 mesh garnet concentrate, 100-180 mesh garnet concentrate and garnet concentrate below 180 mesh in turn; the concentrates are uniformly mixed with cement, cellulose ether and dispersible rubber powder, and then mixed with water to obtain a cement-based adhesive.

[0081] Comparative Example 1-2

[0082] A similar process to Example 1 is adopted, except that the garnet concentrate J1 is replaced by tungsten tailings and quartz sand respectively; and a cement-based adhesive is obtained.

[0083] The types and amounts of the components in the examples and comparative examples are shown in Table 2.

[0084] Table 2

[0085]

[0086]

[0087] Test Example 1

[0088] The cement-based adhesives obtained in the above-mentioned embodiments and comparative examples were tested according to the method specified in JC / T547-2017 Ceramic Tile Adhesives, and the results are shown in Table 3.

[0089] Table 3

[0090]

[0091] It can be seen from the above results that the present invention does not need to further purify the garnet concentrate by strong magnetic separation, and further improves the comprehensive utilization rate of tailings. In addition, the garnet concentrate provided by the present invention is applied to tile adhesives, and the prepared tile adhesive product has excellent performance exceeding the standard requirements of C1-ordinary cement-based adhesives in JC / T547-2017 ceramic tile adhesives, and has equivalent or even better performance than the traditional solution using quartz sand, and quartz sand is expensive. The present invention can significantly reduce the production cost of tile adhesives.

[0092] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A garnet concentrate, characterized in that: The garnet concentrate contains the following components in percentage by mass: 60-80% of garnet, 15-30% of quartz, 3-5% of feldspar, 1-2% of calcite, 0-2% of fluorite, 0-1% of mica, 0-1% of mud minerals, 0-0.5% of iron sulfide minerals, and 0-0.5% of iron non-sulfide minerals.

2. The garnet concentrate according to claim 1, characterized in that: The argillaceous mineral is selected from at least one of chlorite, kaolin and illite; And / or, the iron sulfide mineral is selected from at least one of pyrite and pyrrhotite; and / or, in the iron sulfide mineral, the mass content of total sulfur is less than 0.1%; And / or, the non-sulfide iron mineral is selected from at least one of limonite, hematite and magnetite.

3. A method for preparing garnet concentrate, characterized in that: The method includes: (1) subjecting the tungsten tailings to primary selection in a spiral chute and secondary selection in a shaking table in sequence to obtain concentrate I and tailings I; controlling the conditions so that the content of mud minerals in the concentrate I is ≤1.0wt%; (2) subjecting the concentrate I to a first weak magnetic separation and a second weak magnetic separation in sequence to obtain a garnet concentrate; the magnetic field strength of the first weak magnetic separation is 0.2-0.4T, and the magnetic field strength of the second weak magnetic separation is 0.45-0.6T.

4. The method according to claim 3, characterized in that The operation of step (1) includes: S1: using a spiral chute to sequentially perform a first roughing and a first concentrating on the tungsten tailings to obtain a concentrate I-1 and a tailing I-1; controlling the conditions so that the content of mud minerals in the concentrate I-1 is ≤6.0wt%; S2: using a shaking table to sequentially perform a second roughing and a second cleaning on the concentrate I-1 to obtain the concentrate I and the tailings I.

5. The method according to claim 4, characterized in that The operation in step (1) satisfies at least one of the following conditions: A. In step S1, the conditions of the first roughing and the first cleaning are independently satisfied: the feed concentration is 25-35wt%, the spiral chute flushing volume is 0.8-1.2t / h, and the feed dry ore volume is 0.2-0.5t / h; B. In step S1, the flushing volume of the spiral chute of the first roughing is lower than that of the first cleaning, and the dry ore feeding volume of the first roughing is higher than that of the first cleaning; C. In step S2, the conditions of the second roughing and the second cleaning are independently satisfied: the feed concentration is 15-25wt%, the shaking table flushing volume is 0.1-0.5t / h, and the feed dry ore volume is 0.05-0.1t / h; D. In step S2, the water flushing volume of the shaking table of the second roughing is lower than that of the second fine concentration, and the dry ore feeding volume of the second roughing is higher than that of the second fine concentration.

6. The method according to any one of claims 3 to 5, characterized in that: In step (1), the tungsten tailings contain the following components in mass percentage: 40-45% garnet, 28-35% quartz, 5-10% feldspar, 1-3% calcite, 2-3% fluorite, 1-1.5% mica, 7-10% argillaceous minerals, 1-3% iron sulfide minerals, and 0.5-1.5% iron non-sulfide minerals.

7. A composition for cement-based adhesive, characterized in that: The cement-based adhesive composition contains the following components in percentage by mass: 60-72% of garnet concentrate, 28-35% of cement, 0.1-0.4% of cellulose ether, and 1-2% of dispersible rubber powder; The garnet concentrate is the garnet concentrate according to claim 1 or 2, or is the garnet concentrate prepared by the method according to any one of claims 3 to 6.

8. The cement-based adhesive composition according to claim 7, characterized in that: The cement-based adhesive composition contains the following components in percentage by mass: 33-37% of 40-70 mesh garnet concentrate, 24-27% of 70-140 mesh garnet concentrate, 3-8% of 140 mesh or less garnet concentrate, 28-35% of cement, 0.1-0.4% of cellulose ether, and 1-2% of dispersible rubber powder.

9. A cement-based adhesive, characterized in that: The cement-based adhesive is prepared by mixing a cement-based adhesive composition with water; The cement-based adhesive composition is the cement-based adhesive composition according to claim 8.

10. Use of the cement-based adhesive according to claim 9 in the field of ceramic tile adhesives.

Citation Information

Patent Citations

  • Application of garnet micro powder serving as filler in epoxy resin adhesive as well as epoxy resin adhesive

    CN104099035A